Antibacterial application of natural and carboxymethylated cashew gum-based silver nanoparticles produced by microwave-assisted synthesis. (1st August 2020) - Araruna, Felipe Bastos; de Oliveira, Taiane Maria; Quelemes, Patrick Veras; de Araújo Nobre, Alyne Rodrigues; Plácido, Alexandra; Vasconcelos, Andreanne Gomes; de Paula, Regina Célia Monteiro; Mafud, Ana Carolina; de Almeida, Miguel Peixoto; Delerue-Matos, Cristina; Mascarenhas, Yvonne Primerano; Eaton, Peter; et al.
Graphical abstract: Highlights: The synthesis using polysaccharides and microwave was effective to produce AgNPs. CCG-capped AgNPs were slightly smaller than those coated with non-modified gum. Antibacterial activity was more effective against Gram-negative bacteria. The effect of CGAgNP and CCGAgNP on the E. coli surface was observed by AFM. Abstract: This study presents a green synthesis route to silver nanoparticles (AgNPs) stabilized with cashew gum (CG) or carboxymethylated cashew gum (CCG) using microwave-assisted synthesis and evaluates their antibacterial activity. The antimicrobial activity was measured by determining the minimum inhibitory concentration (MIC) with Staphylococcus aureu s and Escherichia coli . In both cases of the presence of CG and CCG, it was found that higher pH lead to more efficient conversion of silver nitrate to AgNPs with well dispersed, spherical and stable particles as well as low crystallinity. CCG-capped AgNPs were slightly smaller (137.0 and 96.3 nm) than those coated with non-modified gum (144.7 and 100.9 nm). The samples presented promising antibacterial activity, especially on Gram-negative bacteria, resulting in significant membrane damage on treated bacteria in comparison to the untreated control, observed by atomic force microscopy. Thus, a quick and efficient synthesis route was applied to produce CGAgNPs and CCGAgNPs with antimicrobial potential.